АКТУАЛЬНІ ПИТАННЯ СУЧАСНОГО РЕФОРМУВАННЯ ГОСПОДАРСЬКОГО ЗАКОНОДАВСТВА - Побіянська, Неллі Борисівна (SUPREMANCE OF LAW, 2019)
The article analyzes the reasons, the main directions of the work on reforming the economic legislation of Ukraine.. The plan of legislative support for reforms in Ukraine is researched as well as modernization of economic law in it. The main directions of work concerning modern reform of the economic legislation are defined. Positive tendencies of recent changes in economic legislation are indicated.